1987
DOI: 10.1007/bf02636994
|View full text |Cite
|
Sign up to set email alerts
|

Flavor improvement of soybean preparations by genetic removal of lipoxygenase‐2

Abstract: Lipoxygenase-mediated oxidation of fatty acids has long been implicated in the production of off-flavors in soybean products. This assumption was tested by use of preparations from soybean lines nearly isogenic to the cultivar Century that lack the lipoxygenase isozyme or isozyme combinations L1, L~, L3, L1 -}-L3, or L 2 -}-L3. Near-isogenic lines were used to ensure that any effects observed were due to elimination of lipoxygenase isozymes, and not to other unrecognized genetic differences between lines. Full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 21 publications
3
61
0
3
Order By: Relevance
“…Our studies coincide with John et al (2008) who also reported a decrease in the soluble protein content under Cd stress in Lemna polyrrhiza L. It is likely that heavy metals have induced lipid peroxidation and fragmentation of proteins due to toxic effects of ROS, which led to the reduction of protein content (Davies et al 1987). However, NO supplementation improved Cd-decreased soluble protein content.…”
Section: Discussionsupporting
confidence: 62%
“…Our studies coincide with John et al (2008) who also reported a decrease in the soluble protein content under Cd stress in Lemna polyrrhiza L. It is likely that heavy metals have induced lipid peroxidation and fragmentation of proteins due to toxic effects of ROS, which led to the reduction of protein content (Davies et al 1987). However, NO supplementation improved Cd-decreased soluble protein content.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, we analyzed genes related to flavonoid biosynthesis, lipoxygenase (LOX), and trypsin inhibitor in adzuki bean and other sequenced legume species, and no significant difference was observed in the gene number ratio (the gene number/the total gene number in the genome) (SI Appendix, Table S16). However, when we checked the expression of the LOX, which are responsible for the beany flavor in soybean (27), we found that their transcriptional amount was markedly lower in adzuki bean than that of soybean (SI Appendix, Fig. S7).…”
Section: Comparison Of Gene Families With Other Sequenced Legume Genomentioning
confidence: 99%
“…The decrease in protein content in L. polyrrhiza may be caused by enhanced protein degradation process as a result of increased protease activity (Palma et al 2002) that is found to increase under stress conditions. It is also likely that these heavy metals may have induced lipid peroxidation in L. polyrrhiza and fragmentation of proteins due to toxic effects of reactive oxygen species led to reduced protein content (Davies et al 1987). …”
Section: Soluble Protein Contentmentioning
confidence: 99%